Anti-cyclic citrullinated peptide antibody titers decrease in rheumatoid arthritis patients treated with tocilizumab: A pilot study. Issue 2 (3rd March 2020) - Noguchi, Atsushi; Yasuda, Shinsuke; Hisada, Ryo; Kato, Masaru; Oku, Kenji; Bohgaki, Toshiyuki; Suzuki, Miho; Matsumoto, Yoshihiro; Atsumi, Tatsuya
Abstract: Objectives: To analyze the effects of tocilizumab on peripheral B-cell subpopulation and its ability to produce anti-cyclic citrullinated peptide (CCP) antibody in patients with rheumatoid arthritis (RA). Methods: Thirteen consecutive RA patients initiated with tocilizumab were enrolled in our prospective study. Anti-CCP antibody titers and clinical parameters were evaluated during treatment. Peripheral blood B-cell subsets were analyzed using flow cytometry according to the Human Immunology Project. Results: Disease activity was significantly improved and anti-CCP antibody titers significantly decreased at week 24 compared to baseline. The percentages of post-switch memory B cells in CD19+ cells transiently increased at week 12, but there was no significant difference in any of the investigated B-cell subpopulations at week 24 compared to baseline. The ratios of post-switch memory to naïve B cells (post-switch/naïve) correlated negatively with anti-CCP antibody titers regardless of the time-points. Conclusion: Our study indicated that tocilizumab has a potential to reduce anti-CCP antibody production presumably by affecting post-switch/naïve ratio, and that anti-CCP antibody titers reflect B-cell distribution/subpopulation. As anti-CCP antibodies are produced in lymph nodes or ectopic lymphoid structures in synovial tissues, not in circulation, transient increment of post-switch memory B cells after tocilizumab treatment may reflect the altered balance of B-cell distribution between circulation and arthritic joints, resulting in suppressed production of anti-CCP antibody in situ .